2022
DOI: 10.1007/s00441-022-03678-x
|View full text |Cite
|
Sign up to set email alerts
|

More than a simple epithelial layer: multifunctional role of echinoderm coelomic epithelium

Abstract: In echinoderms, the coelomic epithelium (CE) is reportedly the source of new circulating cells (coelomocytes) as well as the provider of molecular factors such as immunity-related molecules. However, its overall functions have been scarcely studied in detail. In this work, we used an integrated approach based on both microscopy (light and electron) and proteomic analyses to investigate the arm CE in the starfish Marthasterias glacialis during different physiological conditions (i.e., non-regenerating and/or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
(146 reference statements)
1
5
0
Order By: Relevance
“…Similarly, a moderate hypertrophy was observed in the nearby haemal sinus, a non-coelomic system of lacunae also involved in immune functions, that contain coelomocytes as well. This phenomenon could be explained by the overuse of the coelomic/coelomic-derived canals for the transport of both molecules and immune or other migrating cells from the neighbor tissues, as suggested by other authors (Hernroth et al 2010;Guatelli et al 2022). The changes in coelomocyte composition that we found during the period of RNC regeneration and discussed below are perfectly in line with this idea.…”
Section: A New Coelomocyte Population Was Detected Trough Fc During R...supporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, a moderate hypertrophy was observed in the nearby haemal sinus, a non-coelomic system of lacunae also involved in immune functions, that contain coelomocytes as well. This phenomenon could be explained by the overuse of the coelomic/coelomic-derived canals for the transport of both molecules and immune or other migrating cells from the neighbor tissues, as suggested by other authors (Hernroth et al 2010;Guatelli et al 2022). The changes in coelomocyte composition that we found during the period of RNC regeneration and discussed below are perfectly in line with this idea.…”
Section: A New Coelomocyte Population Was Detected Trough Fc During R...supporting
confidence: 89%
“…The origin of the P3 coelomocyte remains unknown. The axial organ (Leclerc and Bajelan 1992), the Tiedemann’s bodies (Kaneshiro and Karp 1980), the hemal organs (Ferguson 1966), and the coelomic epithelium (Guatelli et al 2022; Sharlaimova et al 2021; Bosshe and Jangoux 1976) were suggested as candidates for the so-called hematopoietic tissue in starfish. Nonetheless, this last tissue is, nowadays, the most accepted tissue candidate to carry out the mentioned functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coelothelium is a pseudostratified myoepithelium with both apical peritoneocytes and subapical, longitudinally orientated myocytes attached to a basal lamina. On the dorsal side of this basal lamina there are several tissue layers that include circumferentially orientated myocytes and have been interpreted as belonging to the dermis [ 28 ], although in A. rubens they are separated from the densely fibrous layer of the inner dermis (see below) by a space delimited by a thin layer of squamous cells ( Figure 4 B,C). In the midline of the dorsalmost body wall, the longitudinal myocyte layer is greatly expanded to form the apical muscle ( Figure 2 and Figure 4 G).…”
Section: Morphological Aspectsmentioning
confidence: 99%